Can they see what it means: visual literacy and biology learning in Lagos State Secondary Schools - Sulaiman, Afolasade A; Nyong, Olufunke E. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Studies have shown that visual learning is dependent on visual literacy since visually literate learners will not merely look at visuals but see meanings. However, it appears very little has been investigated on this report in Nigerian context. Thus this study examined the effect of visual learning in Biology with the hope of highlighting the effect of visual literacy on performance and pointing out the implications for teaching and counselling. The design was a comparison group pre-test post-test design and 240 students were randomly selected from four secondary schools in Lagos State. The reliability and validity of the instrument; Visual Literacy Scale (VLS) was 0.80 and 0.89. Pre-test results of both groups, revealed no significant difference t (238) = .14, p = .88 > 0.05 in visual literacy level of respondents as majority, 87% demonstrated low level of visual literacy in Biology. No significant difference was also found for sex, t (238) = .749, p = .454 > 0.05 but visual literacy was found to have significant effect on academic performance, t (238) = 21.16, p = .000 < 0.05. These findings suggest the need for teachers to be more inclined to not just teaching biology but teaching visual literacy skills and counsellors to rise up to the challenge of providing preventive and proactive intervention.